Limit analysis and plastic behaviour of piping products / Beh Lee Ching - 428471 Beh, Lee Ching (Skudai : Universiti Teknologi Malaysia, 2002)
Project Paper (Bachelor of Engineering (Mechanical) - University Teknologi Malaysia, 2002